"Agricultural Chymistry is at present in it's infancy": The Board of Agriculture, The Royal Institution and Humphry Davy. (November 2015) - James, Frank A. J. L.
Abstract : In this paper I sketch the institutional interactions between the Board of Agriculture and the Royal Institution in the late eighteenth and early nineteenth centuries. This includes analysing the composition of memberships and committees of both bodies in which, inter alia, I challenge Morris Berman's account of their institutional relations. A key figure was Humphry Davy who, because of his career ambitions, occupied a slightly uncomfortable position as Professor of Chemistry to both organisations. Davy's lecture notebooks and his subsequent publication Elements of Agricultural Chemistry reveal that he drew almost all his direct knowledge of the subject from Britain and Ireland. Yet, despite such parochial shortcomings that might be expected of an infant science at time of war, the popularity of his book, particularly in North America, provided continuity between the end of the Board of Agriculture in 1822 and the start of the impact of Justus Liebig's work in the 1840s.